Perspektif Teologi Islam dalam Masyarakat Modern - Ghaffar, Abd. (Media Akademika, 2002)
The Islamic theological institution was expected later to be quite capable of serving as a bridge between the old world and the newÂ and of working out a new system of thought that could be representative of the best in modern Islamic sciences. According to this statement, the needs of Islamic studies were essentially an evolutionary and progressive programme of instruction which side by side with preserving its spirit, purpose and the fundamental science, should also keep steadily changing and developing. In this case, the Islamic theology should be accepted in the large part of the modern Muslim community. Therefor, the theology of natural law (Sunnatullah)–as for me–is one of the terms in the Islamic theologies which whould be suitable and acceptable to the modern Muslim community.